(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe how teachers at SMP Negeri 1 Tuhemberua adapted their teaching strategies in response to the curriculum shift from the 2013 Curriculum (K-13) to the Kurikulum Merdeka (Independent Curriculum). The study employed a qualitative approach using a descriptive method. The research subjects included the vice-principal for curriculum affairs, teachers, and students. Data were collected through interviews, observations, and document analysis, and subsequently processed through stages of data reduction, data presentation, and conclusion drawing. The results indicate that teachers adapted their teaching strategies across the planning, implementation, and evaluation phases of instruction. These adaptations were evidenced by the alignment of teaching modules with learning outcomes and student characteristics, the implementation of more student-centered learning—utilizing discussions, group work, and projects—and the use of diverse assessment methods that consider both the learning process and outcomes. During implementation, teachers encountered challenges such as limited understanding of the curriculum, time constraints in preparing instructional materials, administrative burdens, and limitations regarding facilities and infrastructure. These challenges were addressed through independent study, peer discussions, time management, and the adjustment of teaching strategies to suit classroom conditions. The findings demonstrate that the curriculum change prompted teachers to gradually adjust their teaching strategies in accordance with curriculum requirements and school conditions.